2021
DOI: 10.3390/cosmetics8020048
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Sources from Aquatic Organisms for Cosmeceuticals Ingredients

Abstract: Long life expectancy of populations in the developing world together with some cultural and social issues has driven the need to pay special attention to health and physical appearance. Cosmeceuticals are gaining interest in the cosmetic industry as their uses fulfills a double purpose: the requirements of a cosmetic (clean, perfume, protect, change the appearance of the external parts of the body or keeping them in good condition) with a particular bioactivity function. The cosmetics industry, producing both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 81 publications
0
17
0
Order By: Relevance
“…In contrast, for acyclolaxaphycins B and B3, the opening is described in the middle of the NRPS gene sequence, suggesting instead that these peptides were obtained by enzymatic degradations. Furthermore, if cyclization were to take place between the amine of Ala 4 and the carboxylic acid of 3-hydroxyleucine 3 , it would also not be possible to obtain [des-(Ala 4 -Hle 5 )]acyclolaxaphycin B and [des-(Ala 4 -Hle 5 )]acyclolaxaphycin B3 as immature products of the biosynthesis.…”
Section: Biosynthesis Of Laxaphycinsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, for acyclolaxaphycins B and B3, the opening is described in the middle of the NRPS gene sequence, suggesting instead that these peptides were obtained by enzymatic degradations. Furthermore, if cyclization were to take place between the amine of Ala 4 and the carboxylic acid of 3-hydroxyleucine 3 , it would also not be possible to obtain [des-(Ala 4 -Hle 5 )]acyclolaxaphycin B and [des-(Ala 4 -Hle 5 )]acyclolaxaphycin B3 as immature products of the biosynthesis.…”
Section: Biosynthesis Of Laxaphycinsmentioning
confidence: 99%
“…Since this date, it has been demonstrated that marine secondary metabolites have a high biological activity and a chemodiversity unequalled at the terrestrial level. These marine natural products can be used in applications such as drugs in the fight against cancer, virus, or bacterial infections but also as cosmetics [1][2][3][4]. Cyanobacteria that represent at least 50% of the aquatic biomass are effective producers of secondary metabolites that can be used as therapeutic agents [5][6][7][8], among which peptides isolated from various strains all over the world [9].…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, the United Nations defined the Sustainable Development Goals to guarantee sustainable consumption and production in order to strongly reduce the global per capita food wastes and to protect marine and maritime environments [16,18]. The need to implement more sustainable practices in the fishery and aquaculture sector necessarily involves the valorization of by-products and discards [19]. Recently, it has been proven that a circular economy approach can be successfully applied to the seafood industry re-using by-products [20].…”
Section: Introductionmentioning
confidence: 99%
“…Marine resources represent a widely available and promising source of unique and active compounds with the potential to produce cosmetics, cosmeceuticals, and nutricosmetics. Among them, seaweeds represent a sustainable and renewable resource, gaining increasing attention for these applications [16,17]. Furthermore, valorization of waste seaweeds, such as beach-casts, which are disposed of in landfills without commercial value, could represent an attractive low-cost source for cosmeceutical industries [18].…”
Section: Introductionmentioning
confidence: 99%